The Effects of Token Arends Learning Model on Communication and Physics Learning Outcomes - Widayanti, Widayanti; Nurviana, Ela; Fatmawati, Alimatu (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to determine whether the Time Token Arends learning model affects communication and physics learning outcomes. All tenth-grade students in one of the high schools in Ogan Komering Ulu Timur became the population, and the sample was determined by random cluster sampling. The research design was the pretest-posttest control group design. The subjects of this research consisted of 58 students. The experimental class implemented the Time Token Arends model, and the control class implemented the conventional model (lecturing and questions and answers). The researchers performed the hypothesis testing using the t-test. Based on the pretest and posttest results, the mean score of the experimental class was higher than the control class. The pretest means a score of the experimental class was 37 and the mean score of the control class was 36. Furthermore, the posttest means a score of the experimental class was 79, and the control class was 64. The mean scores difference indicated a significant effect of the Time Token Arends learning model. The results were supported by the tobserved value greater than the tcritical value, namely 22.02 greater than 1.67. Therefore, H0 was rejected, and Ha was accepted. The percentage of student communication increased significantly after the Time Token Arends model was applied. Future researchers need to develop appropriate instruments to measure scientific communication and student learning outcomes during the current pandemic. During the coupons distribution session, it is necessary to ensure that all students receive coupons without exception.